A Study on Satisfaction Level of Farmers towards Production and Marketing of Agricultural Products - Kathirvel, N. (Indian Journal of Marketing, 2009)
Indian farmers are unable to secure a fair deal at these two stages and an average farmer is denied the full fruits of his industry. The farmers needs the services of well organized marketing system supported by marketing co-operatives, integrated means of transport and scientific storage facilities. The proportion of small holdings (<2) ha in the total number of holdings increased from 68 percent to 86 percent, which in actual terms has more than doubled from 38 million to 87 million during this period. The economic development of a country depends on the development of the core industry in which the majority of its people have been engaged for quite a long time. Fruits and Vegetables is a good source of carbohydrates, proteins, vitamins and mine. Primary data required for the study were collected from the 500 selected respondents of Karur district in order to analyze the technical efficiency of the farmers. The following descriptive statistics Percentages, mean and standard deviation, scaling technique preliminary analysis of data.The general objective of the study is to examine the satisfaction level of production and marketing of agricultural commodities. The study is a combination of both descriptive and analytical. The study is a combination of both descriptive and analytical. The uneconomic holdings may be converted into economic holdings through Co-operative farming. The cultivation is higher in Karur District. But they fetch only lower price. If a Co-operative marketing society is established in this District, it will be beneficial for agricultural producers as it undertakes the procurement, processing and other marketing functions for the benefit of the members.